Haunted dreams : fantasies of adolescence in post-Soviet culture - Kaminer, Jenny (Northern Illinois University Press, an imprint of Cornell University Press, 2022)
"This book analyzes representations of adolescence in Russian culture-including in prose, film, drama, and television-in the period since the end of the Soviet Union in 1991"-- Provided by publisher.
Keywords: Teenagers in mass media.; Mass media and teenagers -- Russia (Federation); Teenagers -- Russia (Federation) -- Social conditions.; Adolescents dans les médias.; Médias et adolescents -- Russie.; Adolescents -- Russie -- Conditions sociales.; Russia & the Former Soviet Union.; Russian & Former Soviet Union.; LITERARY CRITICISM.; Drama.; Europe.; HISTORY.; Mass media and teenagers; Teenagers in mass media; Teenagers -- Social conditions; Russia (Federation); Russia's adolescent turn, adolescence in Russia since 1991, protests against the regime of Vladimir Putin 2017, adolescent protagonist in literature, Russian tv show school, adolescent protagonist in television and film.; Electronic books.